Hydrological function of rewetted peatlands linked to saturated hydraulic conductivity in Kubu Raya, West Kalimantan, Indonesia - Mahardika, Rabbirl Yarham; Tarigan, Suria Darma; Baskoro, Dwi Putro Tejo; Lovita, Vinni; Gangga, Adi; Asyhari, Adibtya; Fatoni, Arif; Jepri, Kristoporus; Ravelle, Adzan Pandu (Brawijaya University, 2024)
The hydrological function of peatlands, one of which is acting as a medium for storing and releasing water, undergoes alteration due to degradation. Saturated hydraulic conductivity (Ks) is a pivotal parameter for comprehending the hydraulic properties of peatlands. Ks plays a crucial role in the transmission and release of water influenced by other peat properties. This research examined the impact of Ks and selected peat properties, namely bulk density and available water content, to depict the hydrological function in rewetted peatlands. The study sites are rubber plantation (RB), oil palm plantation (OP), and drained secondary forest (SF). Results revealed a significantly higher Ks in OP (106.7 cm hr-1) compared to RB (19.56 cm hr-1) and DSF (15.1 cm hr-1). The hydrological function at all study sites was categorized as high, with minor degradation in OP and moderate degradation in RB and SF. Nonetheless, these findings necessitate fundamental interpretation and adjustment. The outcomes of this study can be utilized to prioritize rewetting efforts in the study sites, emphasizing the importance of prioritizing immature peat (fibric) with high Ks.